Acute Treatment of Open Foot and Ankle Fractures Using a Bioartificial Dermal Regeneration Template and Split-Thickness Skin Grafting: A Report of 2 Cases. Issue 2 (April 2019) - McMillan, Logan J.; Parikh, Harsh R.; Cunningham, Brian P.
Abstract : Case: Two patients with open foot and ankle fractures were treated with aggressive irrigation and debridement and acute placement of a dermal regeneration template (DRT) followed by split-thickness skin grafting. Patient 1 was an 82-year-old female with a type IIIB open ankle fracture complexed with 2 significant regions of soft tissue loss. Patient 2 was a 54-year-old male with type IIIB open metatarsal fractures. Both patients healed without complication. Conclusions: Complex open fractures in lower extremities can be managed with acute DRT application. This may be a more cost-effective solution compared to free flaps.